Practice supervision and assessment in nursing, health and social care - Wareing, Mark (New York, NY : Routledge, 2024)
This is an essential guide for all health and social work practitioners supporting an increasing number of learners, trainees, apprentices and pre-registration students engaging in practice-based and work-based learning. Applying educational learning theory to underpin the role and practice of the contemporary practice supervisor, assessor and educator, this accessible book presents strategies for practice learning and personal development. Acknowledging the problematic nature of learning within the workplace, the authors place the lived experience of the learner at the heart of this text and emphasise the critical importance of an expansive and compassionate learning environment for all. The book includes chapters on the context of practice learning, the role of the supervisor/assessor and educator, learning environments, coaching, assessment and supporting the learner in difficulty, among others. It also spotlights practice learning in a range of settings, from working with children, through social care and maternity care. Each chapter includes learning outcomes and activities, as well as a chapter summary. Designed for nurses, midwives, social workers, therapists and operating department practitioners who support learners in the workplace, this text is particularly relevant to registrants completing practice supervisor/assessor/educator preparation and pre-registration students taking modules on supporting learning.
Keywords: Nursing -- Study and teaching; Nursing -- Practice; Nurses -- Supervision of; MEDICAL / Nursing / General; MEDICAL / Allied Health Services / General; MEDICAL / Nursing / Maternity, Perinatal, Women's Health